Ancestral Force in Iconic Imagery: Death and Continuance in a South China Village - Aijmer, Göran (Journal of Chinese religions, 2017)
This essay discusses idioms of continuance in a village in southeast China, based on what was recorded some one hundred years ago by an American sociologist, Daniel Harrison Kulp II, and his research team. This discussion is focused on the cult of the dead with a bearing on the construction of a powerful past influencing the building of a future, in terms of both agricultural production and the creation of new children. The discussion suggests that the iconic imagery of ancestral force as propelling the vegetative power of the earth was transformed here along with certain changes in the productive order, while the social aspect of the dead as constructors of the future lineage community remained conservatively intact, despite some dramatic innovations in the operational order. It also suggests that the strong canopy of agnatic ideology expressed in the cult of the dead found a counterpoint in a local temple.